Root regrowth in single tooth recession using Mucograft® collagen matrix compared to autogenous graft: a literature review (Research, Society and Development, 2023)
The treatment of gingival recession besides providing greater comfort to the patient by reducing sensitivity, restores the normal positioning of the gingival tissue and improves aesthetics. Fast surgical procedures with less painful symptoms would be ideal in clinical practice for root coverage. Thus, biomaterials substitutes to autogenous grafts are increasingly being researched. Thus, the aim of this study is to verify under review of the updated scientific literature, clinical articles that performed root coverage in single tooth recessions using Mucograft® compared to autogenous grafts. For this, the term Mucograft® was used for searches in Pubmed and Google, and 48 results were obtained. Of these, 9 articles were selected. 6 studies evaluated the percentage of root coverage, while 2 evaluated the increase in the range of keratinized tissue and 1 the histological changes. The use of Mucograft® showed positive results regarding the ability of root coverage with good aesthetics and level of postoperative pain similar to that obtained by autogenous grafting. Scientific evidence shows that Mucograft® Matrix is a promising material, but longer follow-up studies are needed to help clinicians in their choices.